Analisis Variabel- Variabel Yang Mempengaruhi Struktur Modal Dan Return On Equity Perusahaan Pada Industri Produk Metal Yang Tercatat di Bursa Efek Indonesia. - Sujoko, * (Program Doktor Ilmu Ekonomi, 2009)
The research is examined empirically the variables predicted significant influence on capital structure and return on equity. The method of sampling used purposive sampling . As much as 8 firm in metal industries is used sample in the research. The period of observation during five years so pooled data.The result of hipotesis testing is indicate that variables of cash flow to total liabilities , earning variability , assets structure, firm size, ROI and tax are significant influence on capital structure and return on equity.The future research is important to conduct to generalized on population. Key Word : Cash Flow to Liabilities, Return On Equity, Earning Variability.